Attachment differences in psychological distress: The mediating roles of filial piety and mindfulness. Issue 4 (6th April 2022) - Huang, Yu‐Lien; Yeh, Kuang‐Hui
Abstract : Evidence for the role of attachment differences in psychological distress is accumulating. Culture may serve as an important influencing factor in this relationship, especially in collectivist societies. We examined the role of two cultural factors relevant to Taiwan: dual filial piety motivations and dispositional mindfulness. Specifically, we investigated whether the associations between attachment insecurities (attachment anxiety and attachment avoidance) and psychological distress (depression, anxiety, and stress) were mediated by dispositional mindfulness and filial piety among Taiwanese emerging adults. We expected that filial piety and dispositional mindfulness might jointly mediate the influence of attachment differences on an individual's level of psychological distress. In total, 302 emerging adults completed the survey questions. After controlling for the mediating effects of filial piety and dispositional mindfulness, attachment anxiety still directly predicts greater depression, anxiety, and perceived stress, but attachment avoidance does not predict psychological distress. Attachment anxiety indirectly predicts greater depression, anxiety, and perceived stress via the mediation of lower dispositional mindfulness, and attachment avoidance indirectly predicts higher depression via lower reciprocal filial piety and lower dispositional mindfulness. Interestingly, we note a negative relationship between attachment avoidance and reciprocal filial piety, which may support the culture‐fit hypothesis that a person's attachment orientation will be more problematic when it is incompatible with cultural values.